Prove that $=\frac{\sin 5 x-2 \sin 3 x+\sin x}{\cos 5 x-\cos x}=\tan x$
We have
${\text{L}}{\text{.H}}{\text{.S}}{\text{.}}\frac{{\sin 5x - 2\sin 3x + \sin x}}{{\cos 5x - \cos x}}$
$ = \frac{{\sin 5x + \sin x - 2\sin 3x}}{{\cos 5x - \cos x}}$
$ = \frac{{2\sin 3x\cos 2x - 2\sin 3x}}{{ - 2\sin 3x\sin 2x}}$
$ = - \frac{{\sin 3x(\cos 2x - 1)}}{{\sin 3x\sin 2x}}$
$ = \frac{{1 - \cos 2x}}{{\sin 2x}}$
$ = \frac{{2{{\sin }^2}x}}{{2\sin x\cos x}}$
$ = \tan \,x = R.H.S$
Prove that $\cos ^{2} 2 x-\cos ^{2} 6 x=\sin 4 x \sin 8 x$
$3\,\left[ {{{\sin }^4}\,\left( {\frac{{3\pi }}{2} - \alpha } \right) + {{\sin }^4}\,(3\pi + \alpha )} \right]$ $ - 2\,\left[ {{{\sin }^6}\,\left( {\frac{\pi }{2} + \alpha } \right) + {{\sin }^6}(5\pi - \alpha )} \right] = $
Let $\frac{\pi}{2} < x < \pi$ be such that $\cot x=\frac{-5}{\sqrt{11}}$. Then $\left(\sin \frac{11 x}{2}\right)(\sin 6 x-\cos 6 x)+\left(\cos \frac{11 x}{2}\right)(\sin 6 x+\cos 6 x)$ is equal to
If $3\cos \theta + 4\sin \theta = 5$ then $3\sin \theta - 4\cos \theta $ is
If $\sin A + \cos A = \sqrt 2 ,$ then ${\cos ^2}A = $